Strategy Marketing Mix Tour Dwisari Water Park in an Effort to Increase Interest in Visiting the East Cikarang Community - Sherly Adellia Firgia Putri; Eman Sulaeman (LPPM Universitas Buddhi Dharma, 2023)
Study this aim for knowing , analyzing , and explaining how to mix strategy marketing tour deep water park dwisari effort increase interest visit Public Cikarang . Study this use type study quantitative with method his research use approach SWOT analysis through IFAS (Internal Factor Analysis Strategy) analysis, EFAS ( External factor Analysis Strategy) Matrix and SWOT Matrix.Sample in study this as many as 33 people consisting out of 30 people who have visit from Tour Dwisari Water Park at least 1 time and 3 Experts. Taking sample with use method Probability Sampling used is Purposive Sampling. based on results research and discussion on available data explained that description internal factors always do optimization to power , in particular vehicle always recreation _ added to make it interesting interest visitor . Whereas factor always external _ do optimization against opportunity with enhancement attractions tour new . From the results of IFAS and EFAS analysis , it shows that the total value of IFAS is 0.60 and the total value of EFAS is 0.40. So the SWOT Matrix is in position Quadrant ? which is interpreted that tour Dwisari Water Park is in a very favorable situation with own opportunities and strengths so that could utilise the opportunities exist . A must strategy applied is support policy aggressive growth .